Impact of Exercise on Anxiety of Sport Science Students of Singaperbangsa University Karawang - Fahreza Muhammad Syandi; Adam Wisnu Fadhillah; Raihan Syakira Prasetya; Muhammad Arief Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to examine the impact of physical exercise on reducing anxiety levels among university students. Anxiety, a negative psychological symptom often triggered by emotional or physical stress, is a common issue faced by students due to academic pressures, social expectations, and future uncertainties. While pharmacological treatments are available, many students seek alternative, accessible, and affordable methods to manage anxiety. Exercise has been shown to provide significant mental health benefits, including anxiety reduction, by releasing neurotransmitters such as endorphins, serotonin, and dopamine, while lowering cortisol levels. This study uses a quantitative experimental approach with a pre-test and post-test design, involving 26 students from the Sport Science at Singaperbangsa University, Karawang. The Hamilton Anxiety Scale (HAM-A) was used to measure anxiety levels before and after a 4-week exercise intervention, consisting of light aerobic and strength exercises conducted once a week. The results indicate a significant reduction in anxiety levels, from a pre-test average score of 28.81 (severe anxiety) to a post-test average score of 5.27 (mild anxiety). The paired sample t-test showed a statistically significant difference (p = 0.000), suggesting that the exercise intervention effectively reduced anxiety. These findings highlight the potential of exercise as a practical, cost-effective intervention for managing anxiety, and recommend its integration into university wellness programs to support students' mental health. Further research with larger, more diverse samples and extended intervention periods is suggested to explore the long-term effects of exercise on anxiety.